The Principles of Designing Hospital Hotel with the Approach of Health Tourism in Kish Island - Kazemha, Anosh Sheikh; Dehkordi, Kaveh Shokoohi (Journal of History Culture and Art Research, 2017)
Medical tourism is known as one of the fastest growing sectors of the world tourism industry. Today, medical tourism has been highly considered by tourists to take advantage of the health benefits and physical and psychological effects of specific areas. Medical tourism as one of the tourism dimensions helps the economy of the country. Given the lucrative nature of the industry, many developing and even developed countries, focus their attention on the industry sector and plan for it. Hospital hotel is a combination of a hotel as a resort and a hospital as a place of healing and rejuvenation that in addition to the course of treatment provides accommodations after treatment as well. Hence, the present study examined the background of this type of application and its advantages and disadvantages and its feasibility in Kish Island to investigate the growth factors and potential of health tourism and ways to overcome obstacles to attract medical tourism. The findings show that the Island faces challenges in basic and health infrastructure, government’s efficient support, having a program for the development of medical tourism, having centers providing the health service with the international credit and promotion and integrated marketing. Proper planning, cheap prices of tourism services, medical education, creating websites of medical tourism and health tourism policy council are also the strategies mentioned in this study.